2005
DOI: 10.1094/phyto-95-1308
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostics, Taxonomy, and Phylogeny of the Stem Nematode Ditylenchus dipsaci Species Complex Based on the Sequences of the Internal Transcribed Spacer-rDNA

Abstract: The stem nematode Ditylenchus dipsaci is of great economic importance worldwide as a parasite of agricultural crops and horticultural plants. The internal transcribed spacer (ITS) of rDNA from 23 populations of the D. dipsaci complex from various host plants were amplified and sequenced. Seven previously studied populations were also included in the study. The phylogenetic analysis of the full ITS and ITS2 sequence alignments using minimum evolution, maximum parsimony, and Bayesian inference under the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 29 publications
12
99
0
1
Order By: Relevance
“…In our previous studies of several nematode groups, the differences in topologies obtained using traditional methods and the models considering secondary structure were conclusive (Subbotin et al 2005(Subbotin et al , 2007. In the present work, however, the phylogenetic trees obtained under different models were not principally different but more resolved, and they are in good accordance with previously published results for heteroderids (Sabo et al 2001;Subbotin et al 2001;Tanha Maafi et al 2003, Madani et al 2004.…”
Section: Phylogeny Of Cyst-forming Nematodes Under the Its2 Structurasupporting
confidence: 92%
See 2 more Smart Citations
“…In our previous studies of several nematode groups, the differences in topologies obtained using traditional methods and the models considering secondary structure were conclusive (Subbotin et al 2005(Subbotin et al , 2007. In the present work, however, the phylogenetic trees obtained under different models were not principally different but more resolved, and they are in good accordance with previously published results for heteroderids (Sabo et al 2001;Subbotin et al 2001;Tanha Maafi et al 2003, Madani et al 2004.…”
Section: Phylogeny Of Cyst-forming Nematodes Under the Its2 Structurasupporting
confidence: 92%
“…Among the presently available 140,000 ITS2 sequences in GenBank, only about 17.9% show the typical fourdomain structure . Using the energy minimization approach and comparative sequence analysis, Subbotin et al (2005) predicted the secondary structure of ITS2 for plant-parasitic ditylenchids, and found that it was displayed as a three-helix structure. The three-domain structure has been observed also in nematodes of the subfamily Anguininae and in several fungi-feeding Ditylenchus species (Subbotin, unpublished).…”
Section: Discussion Prediction Of the Its2 Secondary Structures For Cmentioning
confidence: 99%
See 1 more Smart Citation
“…India: Northeast, dG = -107 kcal/mol differences in their nucleotide length ). Only 17.9 % of the available ITS2 sequences in the public databases show the four-domain structure , though three-helix models are also available (Subbotin et al 2005). Schultz et al (2005) attributed several reasons for the absence of the four-helix structure-firstly, the chosen consensus structure may be very conservative to avoid false positives; secondly, the low abundance of the consensus structure could be caused by the fold prediction itself as only the minimal energy structure was considered and this might not represent the biological active form.…”
Section: Discussionmentioning
confidence: 99%
“…Both ITS1 and ITS2 transcripts appear to fold into the multibranched closed loop Previously, it has been proven in eukaryotic organisms including nematodes that the ITS2 transcript, which is part of the 5Á8S-28S pre-RNA molecule, tends to fold into a multibranched closed loop (Subbotin et al, 2005;Marek et al, 2010). Using an energy-minimization approach, this study shows that the ITS2 transcript of the Czech isolate of B. vallesianus also folds into the multibranched loop with three helical domains (I to III) and with the stem (basal) helix that is formed by perfect complementary pairing of 5Á8S and 28S rRNA molecules (Fig.…”
Section: Specific Sequence Features and Phylogenetic Relationshipsmentioning
confidence: 99%